A multifunctional chitosan composite aerogel for PPCPs adsorption. (15th December 2022) - Zhang, Wenkun; Huang, Ting; Ren, Yu; Yang, Shuai; Zhao, Xinyao; Yuan, Maosen; Wang, Jinyi; Tu, Qin
Abstract: Pharmaceuticals and personal care products (PPCPs) are gaining attention due to their persistence in the environment. Therefore, the development of novel adsorbents to remove them is strongly anticipated. In this study, an improved dual ice-template assembly method had been used for the preparation of ZIF-67/QGO/SB-CS aerogel through ZIF-67, benzoquinone-modified graphene oxide (QGO), and sulfobetaine-modified chitosan (SB-CS) for the adsorption and removal of PPCPs in water. We reported for the first time that the chitosan composite aerogel has antifouling, bacterial filtration and oil-water separation abilities with excellent PPCPs adsorption performance and reusable, which would be a viable option for long-lasting adsorbents for PPCPs in water. Graphical abstract: Unlabelled Image